Fiber optic fabry-perot micro-displacement sensor based on low-cost polymer film (2020)
This manuscript experimentally validates a thin-film polymer andmultimode fiber optic interaction-based low-cost optical fiber displacement sensor. The sensing setup is operated by deflecting a commerciallyMylar® polymer film using multimode optical fiber. The sensor exhibits a higher sensitivity of 24nm/μmand resolution of 41.6nm. The sensor’s analyses also demonstrate good polynomial approximation, with a maximal adjusted square of R = 0.9801, and high stability, in which minimal power (0.4dB-Hour) and wavelength (<2nm-Hour) variations are observed. Moreover, thermal experiments prove that the sensor has lower temperature traits (0.05μm/ C), and this parameter can be distinguished considering the wavelength shifting direction. The simplicity of the scheme, as well as the cost of the elements involved, make this technique a reliable alternative to detect microdisplacements.